Comparison of Success Rates between Two Video Laryngoscope Systems Used in a Prehospital Clinical Trial. (3rd April 2014) - Burnett, Aaron M.; Frascone, Ralph J.; Wewerka, Sandi S.; Kealey, Samantha E.; Evens, Zabrina N.; Griffith, Kent R.; Salzman, Joshua G.
Abstract Objectives. The primary aims of this study were to compare paramedic success rates and complications of two different video laryngoscopes in a prehospital clinical study. Methods. This study was a multi-agency, prospective, non-randomized, cross over clinical trial involving paramedics from four different EMS agencies. Following completion of training sessions, six Storz CMAC™ video laryngoscopes and six King Vision™ (KV) video laryngoscopes were divided between agencies and placed into service for 6 months. Paramedics were instructed to use the video laryngoscope for all patients estimated to be ≥ 18 years old who required advanced airway management per standard operating procedure. After 6 months, the devices were crossed over for the final 6 months of the study period. Data collection was completed using a telephone data collection system with a member of the research team (available 24/7). First attempt success, overall success, and success by attempt, were compared between treatment groups using exact logistic regression adjusted for call type and user experience. Results. Over a 12-month period, 107 patients (66 CMAC, 41 KV) were treated with a study device. The CMAC had a significantly higher likelihood of first attempt success (OR = 1.85; 95% CI 0.74, 4.62; p = 0.188), overall success (OR = 7.37; 95% CI 1.73, 11.1; p = 0.002), and success by attempt (OR = 3.38; 95% CI 1.67, 6.8; p = 0.007) compared to KV. Providers reverted to direct laryngoscopy in 80% (27/34) of the video laryngoscope failure cases, with the remaining patients having their airways successfully managed with a supraglottic airway in 3 cases and bag-valve mask in 4 cases. The provider-reported complications were similar and none were statistically different between treatment groups. Complication rates were not statistically different between devices. Conclusion. The CMAC had a higher likelihood of successful intubation compared to the King Vision. Complication rates were not statistically different between groups. Video laryngoscope placement success rates were not higher than our historical direct laryngoscopy success rates.